New records of long-legged flies (Diptera, Dolichopodidae) from Morocco - Mohamed Nourti; Igor Ya. Grichanov; Kawtar Kettani (Acta Biologica Sibirica, 2019)
This paper provides new data on the distribution of 39 long-legged fly species (Diptera, Brachycera, Dolichopodidae) belonging to 19 genera from Morocco. Twelve species, Gymnopternus assimilis (Staeger, 1842), Hercostomus apollo (Loew, 1869), Hercostomus morenae (Strobl, 1899), Medetera media Parent, 1925, Medetera pallipes (Zetterstedt, 1843), Medetera petrophiloides Parent, 1925, Medetera aff. roghii Rampini et Canzoneri, 1979, Micromorphus minusculus Negrobov, 2000, Sciapus aff. negrobovi Naglis et Bartak, 2015, Campsicnemus simplicissimus Strobl, 1906, Sympycnus pulicarius (Fallén, 1823), and Syntormon pilitibia Grichanov, 2013 are newly added to the Moroccan insect fauna. In addition, available information on geographical distribution for each species is also included.